2019
DOI: 10.3390/ph12030119
|View full text |Cite
|
Sign up to set email alerts
|

Role of Dietary Flavonoids in Iron Homeostasis

Abstract: Balancing systemic iron levels within narrow limits is critical for human health, as both iron deficiency and overload lead to serious disorders. There are no known physiologically controlled pathways to eliminate iron from the body and therefore iron homeostasis is maintained by modifying dietary iron absorption. Several dietary factors, such as flavonoids, are known to greatly affect iron absorption. Recent evidence suggests that flavonoids can affect iron status by regulating expression and activity of prot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
28
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(29 citation statements)
references
References 107 publications
(130 reference statements)
0
28
0
1
Order By: Relevance
“…Quercetin's role in iron absorption, however, is still debatable as quercetin reduces ferroportin activity and, consequently, iron efflux to the bloodstream. This, in turn, induces an accumulation of quercetin-iron complexes in the mucosa that are lost daily by mucosal exfoliation [111,112]. Many iron chelators show anti-inflammatory activities because they can deprive immune cells of iron as well as block its uptake by invading bacteria.…”
Section: Nutritional Sources That Hinder Iron Absorptionmentioning
confidence: 99%
“…Quercetin's role in iron absorption, however, is still debatable as quercetin reduces ferroportin activity and, consequently, iron efflux to the bloodstream. This, in turn, induces an accumulation of quercetin-iron complexes in the mucosa that are lost daily by mucosal exfoliation [111,112]. Many iron chelators show anti-inflammatory activities because they can deprive immune cells of iron as well as block its uptake by invading bacteria.…”
Section: Nutritional Sources That Hinder Iron Absorptionmentioning
confidence: 99%
“…Granado-Serrano et al (2012) demonstrated that quercetin can activate the Nrf2 pathway by supporting nuclear translocation and its transcriptional activity [ 95 ]. Given that the levels of ferroportin (FPN) and ferritin are overexpressed transcriptionally by the Nrf2 pathway, quercetin could affect iron homeostasis and help cells to fight against oxidative stress [ 96 ]. Prenatal exposure of mice to quercetin resulted in increased hepatic iron deposits and induced overexpression of hepcidin to adults [ 77 ].…”
Section: Natural Antioxidants In Iron Overload Treatmentmentioning
confidence: 99%
“…However, the precise site of iron chelation by quercetin is unknown. It is not known whether chelation occurs in the duodenal lumen or in the cytosol of duodenal enterocytes [ 96 ].…”
Section: Natural Antioxidants In Iron Overload Treatmentmentioning
confidence: 99%
“…However, it should be noted that dietary iron is present in two chemical forms—as heme and nonheme—which differ in their bioavailability and uptake [ 24 ]. Heme iron, derived from animal products, is absorbed up to 25–35% [ 25 ], whereas nonheme iron, derived from both animal and plant products [ 26 ], is absorbed much less, in the range of 2–20% [ 27 ]. The greater efficiency of absorption of heme iron results from specific transporters that allow it to pass directly across cell membranes and into the bloodstream, while these transporters cannot be utilized by nonheme iron and require ferric iron (Fe 3+ ) to be reduced to ferrous iron (Fe 2+ ) prior to absorption [ 28 ].…”
Section: Introductionmentioning
confidence: 99%